The acute adaptation of skin microcirculatory perfusion in vivo does not involve a local response but rather a centrally mediated adaptive reflex - Monteiro Rodrigues, Luís; Rocha, Clemente; Andrade, Sérgio; Granja, Tiago; Gregório, João (Frontiers in Physiology, 2023)
Introduction: Cardiovascular homeostasis involves the interaction of multiple players to ensure a permanent adaptation to each organ’s needs. Our previous research suggested that changes in skin microcirculation—even if slight and distal—always evoke an immediate global rather than “local” response affecting hemodynamic homeostasis. These observations question our understanding of known reflexes used to explore vascular physiology, such as reactive hyperemia and the venoarteriolar reflex (VAR). Thus, our study was designed to further explore these responses in older healthy adults of both sexes and to potentially provide objective evidence of a centrally mediated mechanism governing each of these adaptive processes. Methods: Participants (n = 22, 52.5 ± 6.2 years old) of both sexes were previously selected. Perfusion was recorded in both feet by laser Doppler flowmetry (LDF) and photoplethysmography (PPG). Two different maneuvers with opposite impacts on perfusion were applied as challengers to single limb reactive hyperemia evoked by massage and a single leg pending to generate a VAR. Measurements were taken at baseline (Phase I), during challenge (Phase II), and recovery (Phase III). A 95% confidence level was adopted. As proof of concept, six additional young healthy women were selected to provide video imaging by using optoacoustic tomography (OAT) of suprasystolic post-occlusive reactive hyperemia (PORH) in the upper limb. Results: Modified perfusion was detected by LDF and PPG in both limbs with both hyperemia and VAR, with clear systemic hemodynamic changes in all participants. Comparison with data obtained under the same conditions in a younger cohort, previously published by our group, revealed that results were not statistically different between the groups. Discussion: The OAT documentary and analysis showed that the suprasystolic pressure in the arm changed vasomotion in the forearm, displacing blood from the superficial to the deeper plexus vessels. Deflation allowed the blood to return and to be distributed in both plexuses. These responses were present in all individuals independent of their age. They appeared to be determined by the need to re-establish hemodynamics acutely modified by the challenger, which means that they were centrally mediated. Therefore, a new mechanistic interpretation of these exploratory maneuvers is required to better characterize in vivo cardiovascular physiology in humans.